Concrete with Improved Chloride Binding and Chloride Resistivity by Blended Cements - Katalin Kopecskó; György L. Balázs (Advances in Materials Science and Engineering)
Durability and service life of concrete structures can be endangered by chloride ions. Two phenomena help to keep control of chloride effects. On one hand cements are able to bind chloride ions by their aluminate clinker phases or by the clinker substituting materials. On the other hand resistivity of concrete against chloride penetration can be improved by careful selection of concrete constituents and production. Detailed results of two series of extensive experimental studies are presented herein. Chloride ion binding capacity of tested cements in decreasing sequence was the following: (1) CEM III/B 32,5 N-S; (2) CEM III/A 32,5 N; (3) CEM II/B 32,5 R; (4) CEM II/B-M (V-L) 32,5 R; (5) CEM I 42,5 N. Test results indicated that the increasing substitution of clinkers by GGBS improves the chloride resistivity in concrete made with the same water to cement ratio. The application of air entraining agent increases considerably the values of Dnssm. Based on the migration coefficients (Dnssm) the following sequence of efficiency was found (from the best): CEM III/B 32,5 N > CEM V/A (S-V) 32,5 N > CEM III/A 32,5 N > CEM II/B-S 42,5 R > CEM II/A-S 42,5 N > CEM I 42,5 N.